Mobile Video Conferencing for Sharing Outdoor Leisure Activities Over Distance. (3rd March 2020) - Neustaedter, Carman; Procyk, Jason; Chua, Anezka; Forghani, Azadeh; Pang, Carolyn
Abstract : Video communication systems work relatively well for family members and friends when they want to converse with each other between their homes. Yet it is much more challenging to share activities using mobile video conferencing in outdoor settings. We explored the design of mobile video conferencing systems that focused on allowing family and friends to participate in outdoor leisure activities together over distance. We created and studied two technology probe setups: shared geocaching and shared bicycling. Both used mobile cameras and streamed audio and video between remote family members or friends as they participated in the activities. Through these design and study explorations, we explore how family and friends make use of mobile video during leisure activities, what elements are important for the design of such systems, and how mobile video for outdoor leisure activities compares and contrasts to video calling in the home and, more generally, while mobile. Our research points to design considerations around camera views, when and how audio and video should be presented, and the privacy concerns of users and how to balance them with the benefit of the technology.